c-Src is required for complex formation between the hepatitis C virus-encoded proteins NS5A and NS5B: a prerequisite for replication - Pfannkuche, Andreas; Büther, Katrin; Karthe, Juliane; Pönisch, Marion; Bartenschlager, Ralf; Trilling, Mirko; Hengel, Hartmut; Willbold, Dieter; Häussinger, Dieter; Bode, Johannes Georg (Hepatology, 2011)
Hepatitis C virus (HCV) is a leading cause of chronic liver disease worldwide and establishes a persistent infection in more than 60% of infected individuals. This high frequency of persistent infection indicates that HCV has evolved efficient strategies to interfere with the adaptive and innate immune response and to occupy and use host cell infrastructure. The present study provides evidence that c-Src, a member of the Src family kinases that participates in many signal transduction pathways, represents an essential host factor exploited for viral replication. c-Src directly interacts with the viral RNA-dependent RNA polymerase (NS5B) via its SH3 domain and with the nonstructural phosphoprotein NS5A via its SH2 domain. Both interactions are required to maintain the protein-protein interaction of NS5A and NS5B, which has been previously demonstrated to be essential for viral replication. Accordingly, HCV genome replication and production of the viral proteins was strongly reduced upon small interfering RNA-mediated knockdown of c-Src or in the presence of the tyrosine kinase inhibitor herbimycin A. This effect could not be rescued by supplementation of the two other ubiquitously expressed Src family kinases Fyn or Yes. - CONCLUSION: Our data suggest that c-Src participates in the formation of an NS5A/NS5B protein complex that is required for efficient replication of HCV.